A Content Analysis of Speech Acts in 'Action Pack 6 ' and Their Appropriateness - Subaihat, Thekrayat Ali (Journal of Educational and Psychological Sciences, 2020)
This study is concerned with the content analysis of speech acts in Action Pack 6. The purpose of this study is to find out the extent to which the speech acts of apology, compliment, greeting, request, and thanking are included in Action Pack 6, and to find out the extent to which the speech acts of apology, compliment, greeting, request, and thanking are appropriate to students' level, age, and interests. The researcher noticed that there was an imbalance in the provision of the speech acts in Action Pack 6, based on the fact that pragmatic competence is one of the vital aspects of communicative competence. Additionally, it would have been valuable if students were provided opportunities to interact with native speakers of English.
Keywords: speech acts; appropriateness; Action Pack 6; jordan